Effect of Dividend Per Share (DPS) and Earning Per Share (EPS) on Stock Prices in Pharmaceutical Sub Sector Companies - Tri Humaerah; Wahab, Abdul; Sultan, Zulkifli (Terbuka Journal of Economics and Business, 2022)
This study aims to determine the effect of Dividend Per Share and Earning Per Share on stock prices in pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange. The types of data used in this study are qualitative and quantitative. And the data source used is secondary with a sample size of 4 companies. The analysis method used is multiple linear regression, correlation coefficient test, determination test, F test and t test. The multiple linear regression equation is Y = 787,831 - 2,928 + 8,737. The correlation coefficient R is 0.776 and the coefficient of determination () is 0.602. In the F test, it is obtained that the F-count is 12.878> F-table 3.59 with a significant level of 0.000 <0.05, which means that DPS and EPS together or simultaneously have a significant effect on stock prices. For the t test on the DPS variable t-count = - 0.614 <t-table 2.109 with a significant level of 0.547> from 0.05, it means that DPS has an effect but is not significant on stock prices, while the t test on the EPS variable t-count = 3.328> t- table = 2.109 with a significant level of 0.004 <from 0.05, it means that Earning Per Share has a significant and significant effect on stock prices in pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange. This the first hypothesis proposed in this study is rejected, while the second and third hypotheses are accepted